Breastfeeding modifies the effects of environment tobacco smoke exposure on respiratory diseases and symptoms in Chinese children: the Seven Northeast Cities Study. (27th August 2015) - Liu, Y.‐Q.; Qian, Z.; Wang, J.; Lu, T.; Lin, S.; Zeng, X.‐W.; Liu, R.‐Q.; Zhu, Y.; Qin, X.‐D.; Yuan, P.; Zhou, Y.; Li, M.; et al.
Abstract: To evaluate the potential effect of interaction between breastfeeding and environmental tobacco smoke (ETS) exposure on respiratory health, we studied 31 049 children (aged 2–14 years) from 25 districts of seven cities in northeast China. Parents of the children completed standardized questionnaires that characterized the children's histories of respiratory symptoms and illness, feeding methods, ETS exposure, and other associated risk factors. Breastfeeding was defined as having been mainly breastfed for 3 months or more. The results showed that the association of ETS exposure with childhood respiratory conditions/diseases was modified by breastfeeding, and the association for nonbreastfed children was stronger than that for breastfed children. In particular, for nonbreastfed children, the odds ratios (ORs) for the effect of current ETS exposure asthma was 1.71 (95% CI: 1.43–2.05); however, the OR for breastfed children was 1.33 (95% CI: 1.20–1.48), indicating that the interactions between breastfeeding and current ETS exposure on asthma were statistically significant ( P  = 0.019). When stratified by school (kindergarten vs. elementary school), breastfeeding was more protective for asthma‐related symptoms among children from kindergarten. In conclusion, this study shows that breastfeeding is associated with smaller associations between ETS exposure and respiratory conditions in children, suggesting that breastfeeding reduces susceptibility to the respiratory effects of ETS.